2020
DOI: 10.1002/app.49568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyethylene glycol molecular weight on cell growth behavior of polyvinyl alcohol/carboxymethyl cellulose/polyethylene glycol hydrogel

Abstract: Polyvinyl alcohol (PVA)/carboxymethyl cellulose (CMC)/polyethylene glycol (PEG) hydrogel scaffolds are synthesized using cyclic freezing/thawing and subsequent γ‐ray irradiation to evaluate the effect of the molecular weights of PEG (200, 400, 1,000, and 2,000) on strength and cell growth behavior of the hydrogels. As the PEG weight increases from 200 to 2,000, the compressive strength and the pore size decreases gradually from 58.0 ± 8.2 kPa to 17.7 ± 6.1 kPa and from 22.7 ± 3.9 μm to 8.5 ± 1.6 μm, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We chose a maleimide functionalized PEG‐based precursor, as our earlier studies showed a fast reaction of liberated thiol groups with maleimide moieties on a multiarm PEG core. Functionalized multiarm PEG is suitable for hydrogel formation as shown in complex and localized hydrogel‐based biomaterials [ 48–50 ] via light‐based crosslinking reactions, [ 51 ] host‐guest interactions, and a variety of click reactions. [ 52–54 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose a maleimide functionalized PEG‐based precursor, as our earlier studies showed a fast reaction of liberated thiol groups with maleimide moieties on a multiarm PEG core. Functionalized multiarm PEG is suitable for hydrogel formation as shown in complex and localized hydrogel‐based biomaterials [ 48–50 ] via light‐based crosslinking reactions, [ 51 ] host‐guest interactions, and a variety of click reactions. [ 52–54 ]…”
Section: Resultsmentioning
confidence: 99%
“…We chose a maleimide functionalized PEG-based precursor, as our earlier studies showed a fast reaction of liberated thiol groups with maleimide moieties on a multiarm PEG core. Functionalized multiarm PEG is suitable for hydrogel formation as shown in complex and localized hydrogel-based biomaterials [48][49][50] via light-based crosslinking reactions, [51] host-guest interactions, and a variety of click reactions. [52][53][54] In a typical enzyme-promoted gel formation, a gelling mixture comprising PEG4MAL, PEG4TDP o , and enzymes in 100 μL tris buffer was monitored for gel formation during incubation at 37 °C.…”
Section: Peg4tdp O Cleavage By Mmp and Gel Formationmentioning
confidence: 99%
“…The swelling capacity of the cellulose hydrogels was also observed to be restricted as a higher amount of ECH crosslinker was used. This was due to the cellulose polymer networks becoming more rigid due to a higher degree of crosslinking, and thus the hydrogel networks have limited expansion [26][27][28]. However, both the optimization by RSM (Figure 2 and Figure 4) and experimental results (Figure 5) showed that the heating gelation condition had produced cellulose hydrogel with a higher swelling property as compared to the freezing method.…”
Section: The Comparison Of the Swelling Ratio Based On The Freezing Methods And The Heating Methodmentioning
confidence: 99%
“…-Generally, the modi ed cotton fabrics with CMC-PEG-EG and those with CMC-PEG-EG/Ag/different CuO NP ratios showed marked improvements in thermal stability with higher T max values than the unmodi ed cotton fabrics. This could be attributed to the presence of chemical crosslinking reactions occurring between cotton cellulose and CMC-PEG-EG/Ag/CuO NP using EB irradiation (Shin et al,2020). The highest enhancement in the thermal stability, for both the rst and second T max , was estimated in the case of modi ed cotton fabrics with CMC-PEG-EG/Ag/different CuO NP ratios.…”
Section: Thermal Stabilitymentioning
confidence: 94%